Pengaruh Penerimaan Pajak Daerah, Retribusi Daerah, dan Laba Badan Usaha Milik Daerah (BUMD) terhadap Pendapatan Asli Daerah (PAD) di Kabupaten/Kota Provinsi Jawa Timur - Hesti Primaningtyas; Muhammad Alhada Fuadilah Habib (Universitas 45 Surabaya, 2024)
This research is motivated by the importance of Original Local Government Revenue in funding the implementation of regional government. High Original Local Government Revenue can be used to fund various development projects at the regional level such as infrastructure, education, health and so on. The focus of this research is to analyze the influence of regional tax revenues, regional levies and profits of Regional Owned Enterprises on Original Local Government Revenue in Regencies/Cities of East Java Province. This research uses a quantitative approach with an associative type of research. The population in this study is data on local original income, regional taxes, regional levies and BUMD profits for 2018-2022 with a population of 190. The data collection technique used is the documentation method using online observation via the website of the Directorate General of Fiscal Balance and the literature study method. The results of data acquisition were subjected to statistical tests using the help of Eviews version 12 software. The results of the research show that (1) Regional taxes, regional levies, and profits of Regional Owned Enterprises profits simultaneously have a significant effect on Original Regional Income in Regencies/Cities of East Java Province, (2) Regional taxes have a significant effect on Original Regional, (3) Regional levies do not have a significant effect on Original Regional Income, (4( Profits of Regional Owned Enterprises have a significant effect on Original Regional Income.